Pitra-yajna Dalam Masyarakat Hindu Di Bali - Endang Sri Hardiati (Berkala Arkeologi, 1994)
In fact, the implementation of yajna is based on the concept of rna {rnam), which is the concept of "debt" known since Rg Veda, which considers the existence of a "debt" of a person (individual) to gods, priests, and ancestors (ancestors). In the books Brahmanas, rnam has an ethical meaning that encompasses all human duties, which are debts to gods, priests, and ancestors, fellow human beings, and to all beings.Rnam is also associated with obedience to all aspects of moral law or dharma.